Trust and Country-of-Origin Effects on Imported-Product Purchase Intention in Cross-Border E-Commerce - Muhammad Aqshel Revinzky Nizar; Cattleya Rejito; Adhadian Akbar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Cross-border e-commerce (CBEC) platforms such as Shopee, Lazada, and TikTok Shop enable consumers to purchase imported products directly, making consumer behavior an increasingly important dimension of international business. This article examines how country-of-origin (COO), consumer trust, consumer ethnocentrism, and consumer animosity shape purchase intention toward imported products in CBEC. Using a narrative conceptual literature review, the study synthesizes relevant literature published between 1982 and 2025 and develops an integrative framework grounded in the Theory of Planned Behavior (TPB). The review indicates that COO effects vary across product categories and market contexts, whereas trust consistently functions as a mechanism for reducing uncertainty in cross-border transactions. Consumer ethnocentrism emerges as a countervailing influence that can weaken favorable evaluations of foreign products, while religiosity and event-specific animosity may intensify resistance toward products associated with particular countries in Indonesia. The findings also indicate that platform characteristics, logistics performance, and interactive digital engagement increasingly shape the formation of consumer trust in CBEC transactions. Product category and geopolitical context further condition the extent to which consumers translate favorable product evaluations into purchase intention. The proposed framework integrates these cognitive, relational, normative, and situational mechanisms and formulates seven theoretical propositions for future empirical testing. The study contributes theoretically by connecting consumer-behavior and international-business perspectives and extending TPB to explain imported-product purchase intention in cross-border digital trade.